TRUTH MANAGEMENT: MEDIA CENSORSHIP OF THE 1981 PROTESTS IN SAP KOSOVO (Heritage, 2025)
One of the most significant events that took place in the Socialist Federal Republic of Yugoslavia was undoubtedly the 1981 protests in Kosovo. However, in accordance with the established practices of the authorities, the news reaching both the domestic public and international audiences was carefully processed and “filtered” to portray the functioning of the state apparatus and the social climate in an idealized manner, thereby facilitating the preservation of the principle of “brotherhood and unity.” Such practices were particularly evident in the media coverage of the demonstrations in the province. Domestic newspapers such as Borba and Jedinstvo reported on these events using deliberately selected language, while foreign journalists—many of whom investigated the situation months later—often encountered insurmountable obstacles in their efforts to convey the true state of affairs to their audiences.
Keywords: SAP Kosovo, demonstrations, 1981, censorship, media